The Influence of Work Motivation and Physical Work Environment towards Employee Performance PT. Rudi Apriadi Lifiah - Rika Asnawati (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study aims to determine the effect of motivation and work environment on the employees' performance at PT. Rudi Apriadi Lifiah Palembang. This study utilized primary data and secondary data obtained through a questionnaire. Respondents in this study amounted to 57 respondents. The method of analysis in this study was multiple linear regression. The results show that motivation (X1) and work environment (X2) simultaneously have a significant positive effect on employee performance (Y). This research is useful for companies to improve employee performance through motivation and work environment.